Down the cyber rabbit hole: whistleblowing as a means to fulfilling moral obligations in cyber space - Hazlina Shaik Md Noor Alam, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper discourses several issues stemming from whistleblowing. These include, but are not limited to, imposition of liability for inaction in the face of wrongdoing, to scrutinising the available legislative protections for whistleblowers. This paper will also discuss whistleblowing in relation to cyber whistleblowing, which essentially means making disclosures on any misconduct that occurs on the internet. Cyber whistleblowing can provide the basic framework for combating misdeeds online, as it forms a central part of cyber security. Whistleblowing has its roots in less than desirable circumstances, often offering little to no benefit to whistleblowers involved. The act of blowing the whistle, all share common traits, to call attention too, and to punish any and all wrongdoings. Legitimising whistleblowing would enormously help to remove the stigma that is often tied to whistleblowers. This would also give rise to more voluntary whistleblowing in relation to cyber security.